The Psychology of Human Thought An Introduction - Sternberg, Robert J.; Funke, Joachim (Heidelberg University Publishing (heiUP), 2019)
The "Psychology of Human Thought" is an "open access" collection of peer-reviewed chapters from all areas of higher cognitive processes. The book is intended to be used as a textbook in courses on higher process, complex cognition, human thought, and related courses. Chapters include concept acquisition, knowledge representation, inductive and deductive reasoning, problem solving, metacognition, language, expertise, intelligence, creativity, wisdom, development of thought, affect and thought, and sections about history and about methods. The chapters are written by distinguished scholarly experts in their respective fields, coming from such diverse regions as North America, Great Britain, France, Germany, Norway, Israel, and Australia. The level of the chapters is addressed to advanced undergraduates and beginning graduate students.